Natural resins of Mexican plant species: current and potential end-uses - Quiroz Carranza, Joaquín Antonio; Magaña Alejandro, Miguel Alberto (Instituto de Ecología, A.C., 2015)
The current state of information on the resin producer Mexican flora, as well as its present and potential applications are reviewed. Plant exudates are regaining their place in the international market and Mexico has a rich coniferous flora, tropical hardwoods and temperate vines, trees, shrubs, and climbing plants which produce resins in varying amounts, having wide application in human activities. Plant exudates are considered minor forest produce (MFP) or non-timber forest products (NTFPs), and could reach or perhaps exceed the economic value of timber production. The 28 plant families mentioned in this review are widely represented in the Mexican flora; they belong to 79 genera which include species that produce resins and are documented in the technical literature. It is necessary to know them deeply in order to identify niche opportunities whether it is in the food industry, leather tanning, processing of varnish, wood preservatives or additives, as they can be viable for the sustainable management of forests and jungles, provided they are used to improve conditions for producers and workers who participate in its transformation.